Correlation of heart rate/ST slope and coronary angiographic findings. Issue 3 (September 1984) - Balcon, R; Brooks, N; Layton, C
Abstract : The heart rate/ST slope was evaluated in 49 patients undergoing routine investigation for possible coronary artery disease. The slope correctly predicted the absence of any 75% stenoses in the seven patients to whom this applied; it was, however, correct for only four of 30 with one stenosis, one of 10 with two, and neither of the patients with three. Distinct slope ranges were not found, and the previously published ranges said to be specific for no significant stenosis and one, two, and three vessel disease were not.